Rancang Bangun Monitoring Tempat Sampah Berbasis Mikrokontroler - Sujono Sujono; Moh Anshori Aris Widya; Firhan Nur Akbar Adfiansyah (Institut Teknologi dan Bisnis (ITB) Semarang, 2024)
Islamic boarding schools, as one of the oldest Islamic educational institutions in Indonesia, play an important role in rural communities. However, Islamic boarding schools often face hygiene problems, especially in waste management. The large number of students produces large volumes of waste, so effective management is needed. The waste management paradigm must now be changed to reduce, recycle and reuse (3R: Reduce, Reuse, Recycle). In the Industry 4.0 era, technology such as microcontroller-based smart trash cans and IoT have become effective solutions. This smart trash can can measure the weight and height of waste in real-time, providing data that can be accessed via smartphone and website, making it easier for waste managers to maintain a clean environment. This smart trash can will be placed at the Denanyar Islamic Boarding School and managed by a non-governmental organization that cares about cleanliness and the use of recycled waste.